Pipeline to gene discovery - Analysing familial Parkinsonism in the Queensland Parkinson's Project. (April 2018) - Bentley, Steven R.; Bortnick, Stephanie; Guella, Ilaria; Fowdar, Javed Y.; Silburn, Peter A.; Wood, Stephen A.; Farrer, Matthew J.; Mellick, George D.
Abstract: Introduction: Family based study designs provide an informative resource to identify disease-causing mutations. The Queensland Parkinson's Project (QPP) has been involved in numerous genetic screening studies; however, details of the families enrolled into the register have not been comprehensively reported. This article characterises the families enrolled in the QPP and summarises monogenic forms of hereditary Parkinsonism found in the register. Method: The presence of pathogenic point mutations and copy number variations (CNVs) were, generally, screened in a sample of over 1000 PD patients from the total of 1725. Whole exome sequencing (WES) was performed on eighteen probands from multiplex families. Results: The QPP contains seventeen incidences of confirmed monogenic forms of PD, including LRRK2 p.G2019S, VPS35 p.D620N, SNCA duplications and PARK2 p.G430D (hom) & exon 4 deletion (hom). Of these seventeen, five belong to multi-incident families, while another eight have a family history of at least one other case of PD. In additional families, WES did not identify known forms of monogenic Parkinsonism; however, three heterozygous mutations in PARK2, p.R275W, p.Q34fs, and a 40bp deletion in exon 3 were identified. Of these three mutations, only the 40bp deletion segregated with disease in a dominant inheritance pattern. Conclusion: Eighteen probands have screened negative for known CNVs and mutations that cause clear monogenic forms of PD. Each family is a candidate for further genetic analysis to identify genetic variants segregating with disease. The families enrolled in the QPP provide a useful resource to aid in identifying novel forms of monogenic PD. Highlights: Reporting the demographics of multiplex families found in the QPP. Summarising previous findings for monogenic parkinsonism found in the QPP. Report preliminary findings of whole exome sequencing of 18 probands from multiplex families.